Design of Green Infrastructure: A Case Study of RGUKT Srikakulam - Jeevan Madapala; Jahnavi Puppala (International Journal of Engineering and Management Research, 2022)
Rainwater harvesting is a promising solution to ensure a year-round water supply, meet agricultural demands and maintain ecological flows in the water system. It is also a viable option to reclaim declining water bodies and offer a sustainable source of water. In correspondence, the study attempts to explore the feasibility of rainwater harvesting through green infrastructure for urban catchments, with an example of the RGUKT Srikakulam university campus in Etcherla. The study attempts to analyze the campus as a catchment for Rainwater harvesting and design green infrastructure solutions in accordance with the site conditions. The study uses the SCS-CN methodology to compute the runoff of the catchment by developing excel spreadsheets, using the rainfall over a 10-year period. The solutions of green infrastructure explore options such as Bio-swales, rain gardens, infiltration strips, permeable pavements, retention basins, detention basins, etc. The purpose of the study is to analyze the feasibility of achieving zero runoff for the entirety of the RGUKT Srikakulam campus for a maximum of 10-year rainfall. The study also attempts to explain the secondary benefits of green infrastructure development. This study aimed to develop simple models to replicate such work for complex and modified urban and semi-urban settings (catchments). When put into practice, these techniques were developed to ensure easy design, construction, and development of green infrastructure solutions with suitability to suit specific requirements of distinctive urban centers. When developed on a full scale, across the country, Green Infrastructure (GI) may act as a solution to renew the groundwater resources and ensure water supply throughout the year.